Muhammadiyah dalam Perkembangan Pendidikan Islam di Indonesia - Azaz Akbar; A. Rezky Nurhidaya S; A.Muh Ali; Syarifuddin Ondeng (Universitas Muhammadiyah Enrekang, 2021)
Muhammadiyah is an organization founded by Kyai Ahmad Dahlan which is mostly engaged in business charities in the field of education such as PAUD/TK, SD, SLTP, SLTA, and Universities. The purpose of this study is to provide a brief review of several research articles that discuss the Muhammadiyah movement from its founding background to its influence in the world of Islamic education in Indonesia. This research method is a literature study because in the end all the material that has been read must be drawn a conclusion in the form of a report. Data sources consist of primary data and secondary data. The results of this study indicate that the emergence of the Muhammadiyah organization is a response to the enforcement of Islamic teachings that depart from the Qur'an and Sunnah. Also of the factors raised from the two studies above are about the purification of monotheism which was influenced by colonialism regarding shirk, superstition, bid'ah and superstition and living in poverty, destitution and ignorance. Muhammadiyah organization is very concerned about the condition of a pluralistic society in the development of the education curriculum in Indonesia.